The Federal System of Government and Nepal in Transition: A Critical Analysis of Provincial Disparities - Silwal , Keshab Raj (Journal of Durgalaxmi, 2025)
Democracy is a global phenomenon widely discussed and embraced across nations, whereas federalism is often regarded as one of its key forms of governance. Democracy creates a conducive environment for the protection and effective realization of human rights, encompassing democratic principles such as human welfare, individual freedom, security, equity, social justice, and public deliberation. The core elements of democracy include a competitive multiparty political system and universal suffrage. In the case of Nepal, with a long history of monarchical rule, it has only recently begun its democratic journey, and its democratic institutions remain in a nascent stage, facing multiple challenges from various directions. The second constituent assembly election was held in 2013, culminating in the promulgation of a new constitution in 2015 that introduced a federal system of governance. The new constitution divided Nepal into seven provinces, further subdivided into 293 municipalities and 460 rural municipalities. Federalism, as a system of governance, seeks to harmonize the relationship between centralized and decentralized authorities by balancing unity with regional autonomy. This paper seeks to explore the intersection of democracy and federalism in Nepal by analyzing the inequalities among the seven provinces. Using an explanatory approach supported by secondary data, it compares the provinces across variables such as population, geography, resources, and socio-economic indicators. The findings reveal significant disparities among the provinces, which hinder the consolidation of democratic principles in Nepal.